2003
DOI: 10.1136/heart.89.10.1245
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of mortality in patients with acute coronary syndrome undergoing percutaneous coronary intervention

Abstract: A cute coronary syndromes (ACS) are a major health problem and account for a large proportion of the total number of hospitalisations in the UK. The question as to whether and when revascularisation is indicated remains controversial and the choice of surgery or percutaneous coronary intervention (PCI) or continued medical treatment is often difficult. Such decisions are critically dependent on the clinician's ability to risk stratify patients at presentation and to calculate the risk of invasive treatments. O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
9
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 4 publications
0
9
0
Order By: Relevance
“…Previously many studies have been conducted to investigate the predictors of mortality of patients presenting with AMI [ 6 11 ]. However, these studies were taken place in western populations with presumably ideal treatment and disease control.…”
Section: Introductionmentioning
confidence: 99%
“…Previously many studies have been conducted to investigate the predictors of mortality of patients presenting with AMI [ 6 11 ]. However, these studies were taken place in western populations with presumably ideal treatment and disease control.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies in the USA and Europe have investigated the predictors of in-hospital mortality post-AMI [ 2 - 7 ]. Several variables were identified related to the clinical characteristics of the patients and their comorbidities [ 3 , 4 , 7 - 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies in the USA and Europe have investigated the predictors of in-hospital mortality post-AMI [ 2 - 7 ]. Several variables were identified related to the clinical characteristics of the patients and their comorbidities [ 3 , 4 , 7 - 10 ]. Similar studies on AMI patients in developing countries are scarce [ 11 ], and little is known about the management and mortality rates of such patients in these countries [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Acute coronary syndrome (ACS) is common, and most patients with ACS are aged 65 and older 1 . Although this condition has been widely studied, older patients are underrepresented in the literature 2,3 . Numerous studies have shown that older patients with ACS have worse outcomes and that age is a major risk factor for a major acute coronary event 4–7 .…”
mentioning
confidence: 99%